Ecoenzymes as Indicators of Compost to Suppress Rhizoctonia Solani. Issue 4 (2nd October 2017) - Neher, Deborah A.; Fang, Lynn; Weicht, Thomas R.
ABSTRACT: Reports of disease suppression by compost are inconsistent likely because there are no established standards for feedstock material, maturity age for application, and application rate. The overall goal of the study was to evaluate a suite of biological indicators for their ability to predict disease suppression. Indicators included both commercial available methods for compost stability (Solvita™, respiration) and metrics of soil ecology not yet adopted by the compost industry (e.g., ecoenzymes, nematode community index). Damping-off by Rhizoctonia solani on radish was chosen as a model system given its global importance, competitiveness affected by carbon quality, and lack of disease management options for organic production. Biological indicators were evaluated for their ability to consistently differentiate among curing process, maturity, and feedstock material as a function of disease severity of a seedling bioassay and a compost extract assay to test competition with R. solani growth. Compost processed as vermicompost and anaerobic digestate were more suppressive against R. solani than windrow or aerated static pile. Mature composts were more suppressive than immature components. Feedstocks containing dairy manure and/or hardwood bark tended to have suppressive qualities. In contrast, poultry manure-based components were conducive to disease. Microbial ecoenzymes active on chitin and cellulose and nematode community indices were better predictors of disease suppressiveness than microbial respiration. These indicators are quicker than plant bioassays and could be adopted as tools to certify commercial products.